There are many ways to solve this problem. All you have to do is simple algebraic manipulation. Solve for b and h with the two simpler equations:
2b = 12; divide 2 on both sides to get b = 6
h - x = 2; add x to both sides to get h = (2 + x)
Plug this stuff into the first equation to solve for x. Once we solve for x, we can plug that x value into the equation for h. Because you can see we didn’t get an actual numerical value for h. So:
x + (2+x) + 6 = 14
Subtract 6 from both sides and distribute that plus sign to get rid of the parenthesis. Then combine the like terms to get:
2x + 2 = 8
Subtract 2 from both sides and divide by 2 to get x = 3
Finally plug it into the equation for h:
h = 2+3 = 5